Tahlil At-Tasybih Fii Kitab Manhaju At-Tullab Fii Thalabil ‘Ilmi Wa Fii Aadab Li Syeikh Ustman Muhammad Sa’id Tungkal - Hardiyanti, Silvira; Zaini, Hisyam (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Balaghah science is a discipline that studies the structure of beautiful Arabic sentences but has a clear meaning. Among the disciplines in balaghah science include: Bayan science, ma'ani and badi which we will discuss in more depth related to bayan science which consists of tasybih, majaz and kinayah The researcher will analyze tasybih based on the presence or absence of tasybih customs The researcher formulates the problems to be studied, namely: 1). What are the tasybih sentences based on the tasybih customs in the book Minhaju At-Tullab Fii Thalabil 'Ilmi Wa Fii Al-Adaab by Sheikh Ustman Muhammad Sa'id Tungkal 2). What are the types of tasybih based on the presence or absence of tasybih customs in the book Minhaju At-Tullab Fii Thalabil 'Ilmi Wa Fit Al-Adaab by Sheikh Ustman Muhammad Sa'id Tungkal 3). What are the objectives of tasybih based on the presence or absence of tasybih customs in the book Minhaju At-Tulliub Fi Thalabil 'Ilmi Wa Fii Al-Adaab by Sheikh Ustman Muhammad Sa'id Tungkal, The purpose of this research is to develop, explore and expand the knowledge of students and readers and make it easier to understand and analyze which are included in the tasybih category in the book Manhaju At-Tullab by Sheikh Ustman Muhammad Sa'id Tungkal The objectives of this research adalalı the book Minhaju At-Tullab by Sheikh Ustman Muhammad Sa'id Tungkal using books related to the science of bayan and tasybih. In the Minhajut Tullab Book, it explains good manners for students of knowledge as well as various histories and monotheism towards Allah and his messengers. In the book Minhaju At-Tullab by Sheikh Ustman Muhammad Sa'id Tungkal, there are several sentences that contain tasybih. The method used is qualitative or the Adapan Library method. This type of research is descriptive research. The results achieved in this research, researchers found 70 verses of poetry containing lasybih including 70 mursal mujmal, with 7 objectives including 26 kasyfu matters musyabah, 4 bayan miqdar matters musyabah, 10 ishol matters musyabah, 15 tazyiin musyabah, 6 tasywiyah musyabah, 2 ihtimam musyabah , and 3 tanwiyah musyabah.